Relationship between Carbon Sequestration and Physico-chemical Properties of Soils in Salt-affected Areas, Northeast Thailand - Islam, Kazi Kaimul; Anusontpornperm, Somchai; Kheoruenromne, Irb; Thanachit, Suphicha (Agriculture and Natural Resources, 2014)
Variation of soil organic carbon as a result of differences in soil physico-chemical properties under natural and agricultural land use systems is of signiﬁ cance for understanding and determining soil organic carbon sequestration (SOCseq). For the objectives of investigating Cseq and its relationship with different physical and chemical soil properties and high concentrations of Na+ salts, this study was carried out in sandy-natured soil areas with salt-contaminated soil distributing in the lower areas of Ban Nong Suang in Kham Thale Sor district, Nakhon Ratchasima province, northeast Thailand. Soil samples were collected for laboratory analysis at four different depths of 0–15, 15–30, 30–45 and 45–60 cm. Three transects (tran-1, tran-2 and tran-3) were chosen, each comprising six mini soil pits located from the upper to the lower part of the transect. Most soils had loamy sand to sandy loam texture, being composed of very low amounts of organic carbon (OC), total N, available P and K in association with high bulk density, low pH and low cation exchange capacity. Some of the soils studied had sodic and saline sodic features with extremely high pH, electrical conductivity, sodium adsorption ratio, exchangeable sodium percentage and base saturation percentage. The percentage of silt+clay had a positive correlation with carbon sequestration (Cseq), whereas bulk density had a signiﬁ cant negative correlation. Total N and available P were highly signiﬁ cantly and signiﬁ cantly positively correlated, respectively, with Cseq, while pH and other exchange properties were negatively correlated. A high concentration of Na+ caused a highly signiﬁ cant depletion of OC in soils, creating extremely hazardous conditions in crop production, especially in low-lying areas of this undulating terrain.